2020
DOI: 10.26811/peuradeun.v8i3.550
|View full text |Cite
|
Sign up to set email alerts
|

Learning for Children with Special Needs of Dyscalculia

Abstract: This study aimed to develop mathematics learning tools to help children with special needs of dyscalculia in elementary school. The procedural development of the device was through a 4-D model consisting of four phases; defining, designing, developing, and disseminating. However, based on the research objectives, this development was limited only to the development stage (develop), which is to the learning device testing activities. So the development of learning tools in this study consisted of three main sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Mathematics is a science taught at school conceptually and thematically that is interconnected with other knowledge in everyday life (Muslihat et al, 2019). Learning mathematics is the formation of a way of thinking in interpreting understanding and reasoning a connection between certain values (Azhari et al, 2020;Julaeha et al, 2020). The knowledge in mathematics is universal (Tuankotta & Jana, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mathematics is a science taught at school conceptually and thematically that is interconnected with other knowledge in everyday life (Muslihat et al, 2019). Learning mathematics is the formation of a way of thinking in interpreting understanding and reasoning a connection between certain values (Azhari et al, 2020;Julaeha et al, 2020). The knowledge in mathematics is universal (Tuankotta & Jana, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Azhari on children with dyscalculia found a mathematics learning model to help children with special needs with dyscalculia in elementary schools to help with their learning difficulties (Azhari et al, 2020).…”
Section: A Introductionmentioning
confidence: 99%
“…Several studies related to children with dyscalculia disorders already exist with various problems that arise. Research by Azhari, Yacoeb and Irfan (Azhari et al, 2020) succeeded in compiling learning tools for children with dyscalculia cases to help them overcome learning difficulties. Another study from Chideridou-Mandari, Padeliadu, Karamatsouki, Sandravelis, and Karagiannidis (Chideridou-Mandari et al, 2016) stated that there needs to be special knowledge for mathematics teachers to understand the unique characteristics of students with dyscalculia disorders to choose the suitable learning model.…”
Section: Introductionmentioning
confidence: 99%